Comparison between CT-enterography and MR-enterography for the diagnosis of right-sided deep infiltrating endometriosis of the bowel. Issue 161 (April 2023) - Collin, Mégane; Barat, Maxime; Oudjit, Ammar; Terris, Benoit; Dohan, Anthony; Rousset, Pascal; Chapron, Charles; Marcellin, Louis; Dousset, Bertrand; Soyer, Philippe
Highlights: Although rare, right-sided bowel deep infiltrating endometriosis is a serious concern as it may require more extensive bowel resection that was not anticipated preoperatively. CT-enterography and MR-enterography have not different sensitivities (52–60% for both) and convey only fair interobserver agreement (κ = 0.37 and 0.31, respectively) but are highly specific (93–99% and 92–99%, respectively) for the diagnosis of right-sided bowel DIE. Computed tomography-enterography and magnetic resonance-enterography used in combination yields a significant incremental gain of 20% in the detection rate of right-sided bowel deep infiltrating endometriosis implants compared to CT-enterography or MR-enterography alone. Abstract: Objective: To compare computed tomography-enterography (CTE) and magnetic resonance-enterography (MRE) in the detection of right-sided bowel deep infiltrating endometriosis (DIE). Materials and Methods: Fifty women with DIE who underwent preoperatively CTE and MRE were included. CTE and MRE were first analyzed separately by two independent readers who analyzed five bowel segments (cecum, appendix, ileocecal junction, distal ileum and proximal small bowel [ i.e., proximal ileum and jejunum]) for the presence of DIE and then interpreted in consensus. CTE, MRE and CTE with MRE were compared in terms of sensitivity, specificity and accuracy. Interobserver agreement was assessed with kappa (κ) test. Results: Using the reference standard 25 out 250 bowel segments were involved by DIE in 18 women and 225 were free of DIE. Sensitivity, specificity, and accuracy of CTE were 60% (95% confidence interval [CI]: 39–79), 93% (95% CI: 89–96) and 90% (95% CI: 85–93) for Reader 1, respectively, and 52% (95% CI: 31–72), 99% (95% CI: 97–100) and 94% (95% CI: 91–97) for Reader 2, with no differences in sensitivity ( P  = 0.564) and specificity ( P  = 0.181) between readers and fair interobserver agreement (κ = 0.37). For MRE these figures were 52% (95% CI: 31–72), 92% (95% CI: 88–95) and 88% (95% CI: 84–92) for Reader 1 and 60% (95% CI: 39–79), 99% (95% CI: 96–100) and 95% (95% CI: 91–97) for Reader 2, with no differences in sensitivity ( P  = 0.157) and specificity ( P  = 0.061) between readers and fair interobserver agreement (κ = 0.31). Significant differences in sensitivity (20%; 95% CI: 7–41) were found between CTE + MRE vs. CTE alone for Reader 1 and vs. MRE alone for Reader 2 ( P  = 0.041 for both) Conclusion: CTE and MRE have not different sensitivities and convey only fair interobserver agreement but are highly specific for the diagnosis of right-sided bowel DIE. CTE and MRE are complementary because they improve the detection of DIE implants when used in combination.